GLOBAL MANAGERIAL ISSUES AND THEIR EFFECT ON OPERATIONAL PERFORMANCE IN SELECTED FAST-FOOD FIRMS IN ABIA STATE - Umeh , Adaobi Nkeiruka; Ezeagu, Obinna Chukwudi (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
This study analysed the effect of global managerial challenges on organizational performance (A study of selected fast-food industry in Umuahia Abia state). The specific objectives included: (a) determine the effect of the leadership behaviour/styles on the survival of fast-foods in Abia State. (b) Examine the extent to which the management structure of fast-foods influences the sustainability of fast-foods in Abia State. (c) determine the effect of work conditions on the profitability of fast-foods in Abia State, and (d) ascertain the effect of managerial competence on the effectiveness of fast-foods in Abia State. Survey research design was adopted. A total of 145 questionnaire was administered to the staff of selected fast-food industry in Umuahia Abia state. Frequency distribution and percentages was determined, the hypotheses were tested using regression analysis and Spearman correlation coefficients with the help of SPSS version 25.0. The findings indicate that; Leadership behaviour/styles has significant effect on the survival of Fast-foods in Abia State., Managerial structure has significant influence on the sustainability of Fast-foods in Abia State., Work conditions has significant effect on the profitability of Fast-foods in Abia state and Managerial competence has significant effect on the effectiveness of fast-foods in Abia State. The study recommended that; CEO/Manager of fast-food should possess good leadership behaviour/styles in order to improve on the survival of Fast-foods in Umuahia as initiating structure and consideration, motivation and vision, employee-oriented and production-oriented, coercion and motivation are variable tools for organizational survival. Finally, there is need to improve and continuously adjust to good and effective managerial structure to help carry out works and other responsibilities effectively and efficiently by employees of Fast-foods in Umuahia Abia state in other to foster maintain their sustainability